Optimasi Radius Server untuk Pengaturan Alokasi Bandwidth pada Jaringan Hotspot - Putra, I Gede Bagus Premana; Pratama, I Putu Agus Eka (JUSS (Jurnal Sains dan Sistem Informasi), 2019)
Hotspot is one form of utilizing Wireless LAN technology that can be used to access internet services and is usually found in public areas such as libraries, campus internet parks, or offices. Aspects that need to be considered in hotspots to make users feel comfortable is security then at the provider side, the aspect that needs to be considered is the regulation of bandwidth allocation to optimize the data transfer speeds that the network and to prevent the possibility of dense network traffic. RADIUS server is one type of server that can be used at hotspots to secure hotspots because it supports various types of encryption. In this study, optimization of the settings for hotspot network bandwidth is optimized by integrating the RADIUS server with RouterOS. Bandwidth allocation management is done by determining the active time of a user account and set quotas hotspot uploads and downloads for the account. The results obtained from this study indicate that when a hotspot user account has passed the active time or has passed the upload quota and the download given, the account will be deleted from the list of hotspot user accounts or disabled.